2022
DOI: 10.7554/elife.72872
|View full text |Cite
|
Sign up to set email alerts
|

Multiple motors cooperate to establish and maintain acentrosomal spindle bipolarity in C. elegans oocyte meiosis

Abstract: While centrosomes organize spindle poles during mitosis, oocyte meiosis can occur in their absence. Spindles in human oocytes frequently fail to maintain bipolarity and consequently undergo chromosome segregation errors, making it important to understand mechanisms that promote acentrosomal spindle stability. To this end, we have optimized the auxin-inducible degron system in C. elegans to remove factors from pre-formed oocyte spindles within minutes and assess effects on spindle structure. This approach revea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 70 publications
(169 reference statements)
1
28
1
Order By: Relevance
“…It has recently been shown that Nuclear Mitotic Apparatus 1 (NUMA1) and the centrosomal proteins (CEP) CEP152 and CEP 55 are key to centrosomal function. The motor proteins kinesin and dynein-dynactin preform key role not only moving chromosomes but also on collecting the ends of microtubules together into cohesive mitotic spindle poles in a bipolar orientation [ 74 , 75 , 142 , 143 , 144 , 145 , 146 , 147 ]. Table 9 lists the EWAS hits identified in the Schrott datasets for some of these proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that Nuclear Mitotic Apparatus 1 (NUMA1) and the centrosomal proteins (CEP) CEP152 and CEP 55 are key to centrosomal function. The motor proteins kinesin and dynein-dynactin preform key role not only moving chromosomes but also on collecting the ends of microtubules together into cohesive mitotic spindle poles in a bipolar orientation [ 74 , 75 , 142 , 143 , 144 , 145 , 146 , 147 ]. Table 9 lists the EWAS hits identified in the Schrott datasets for some of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, as explored in some detail in the Discussion section, the exact mechanism of this is not understood in molecular terms. Perhaps the most likely explanations relate to disruptions of the post-translational modification code on either the tubulin which comprise the microtubules along which the chromosomes are pulled by cellular kinesin motors [ 74 , 75 , 76 ], the 90 proteins of the mammalian kinetochore which bind the chromosomes to the microtubules [ 77 ], or to the centrosomal chromatin itself [ 77 ]. Chromosomal scission and one or two whole genome doubling events [ 78 ] are also described as part of cannabinoid genotoxicity [ 79 ] all of which suggest gross disruption of the meiotic I machinery of spermatid division.…”
Section: Introductionmentioning
confidence: 99%
“…Our experiments demonstrated that an inward force exists, because the metaphase spindle rapidly shortened and then collapsed upon KLP-18 inhibition. Moreover, we recently found that dynein provides an inward force on the oocyte spindle, suggesting that it could antagonize KLP-18 ( Cavin-Meza et al. , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2017 ; Mullen and Wignall, 2017 ); because KLP-18 sorts microtubule minus ends outward during spindle assembly and is required for maintaining spindle length in metaphase, it is possible that it also exerts outward force to drive microtubule sliding during anaphase B. We recently found that when KLP-18 and dynein are both depleted, anaphase B can still occur ( Cavin-Meza et al. , 2022 ), demonstrating that this motor is not essential for outward sliding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation